The Indonesian Government's Readiness to Develop the Halal Food Industry in the Metaverse Era - Susanti, Dyah Ochtorina; Sari, Nuzulia Kumala; Adonara, Firman Floranta; Tektoka, Rahmadi Indra; Putri, Auliya Safira (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
The halal food industry in its development in the metaverse era has great and promising potential. Especially for Indonesia as a country with the largest Muslim population in the world. This is a challenge for the Indonesian government in welcoming the development of the halal food industry and making Indonesia the center of the world's halal industry. The research method used is empirical juridical with a qualitative approach. The results of this research show that in welcoming the development of the halal food industry, support from Bank Indonesia and the Government is needed, in the form of regulations, especially in accommodating provisions and fatwas related to the halal food industry so that it enters the legal hierarchy and has sufficient power.